2011
DOI: 10.1166/jbn.2011.1234
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystallization of Poorly Water Soluble Drugs for Parenteral Administration

Abstract: Approximately 50% active substances discovered by combinatorial chemistry and high-throughput screening show poor solubility in water. Out of various available approaches "Nanoedege technology" (Combination of Precipitation and Homogenization) was selected. Amphotericin B (Amp B) was used as a model drug. Three different preparations of Amp B were produced by using three different surfactants Tween80, Pluronic F68, Soya Lecithin and assessed for their efficacy and stability. In this study the Amp B nanosuspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On similar lines, Zakir et al 134 recently reported amphotericin B nanocrystal-based formulation for parenteral administration. They have used Tween 80, Pluronic ® F68 and Soya lecithin as the stabilizers to achieve stability and desired particle size range.…”
Section: Parenteral Nanosuspensionmentioning
confidence: 84%
See 1 more Smart Citation
“…On similar lines, Zakir et al 134 recently reported amphotericin B nanocrystal-based formulation for parenteral administration. They have used Tween 80, Pluronic ® F68 and Soya lecithin as the stabilizers to achieve stability and desired particle size range.…”
Section: Parenteral Nanosuspensionmentioning
confidence: 84%
“…They have used Tween 80, Pluronic ® F68 and Soya lecithin as the stabilizers to achieve stability and desired particle size range. Nanocrystal formulation for the parenteral administration with smaller particle size was successfully produced with the NanoEdge TM technology 134 . The technology utilizes basic precipitation process followed by annealing step applying high energy either in the form of shear or thermal energies 33 .…”
Section: Parenteral Nanosuspensionmentioning
confidence: 99%
“…The number of poorly soluble drug compounds has increased sharply since high-throughput screening and combinatorial chemistry were introduced into pharmaceutical development processes. [ 1 2 3 ] Enhancing the oral bioavailability of poorly water-soluble drugs by an increasing dissolution is one of the most challenging tasks in drug development. [ 4 5 ] The various methods such as salt formation, solubilization, particle-size reduction, and solid dispersion (SD) formation have been reported for this purpose.…”
Section: Introductionmentioning
confidence: 99%